Socialno-emocionalno funkcioniranje in staranje - Svetelšek, Ajda (Kakovostna starost, 2017)
The scientific research of social and emotional functioning is important, because it has a great impact on the nature of interpersonal relationships. The satisfaction with interpersonal relationships is of great importance for well-being of every individual. Previus research has shown, that social and emotional functions stay very well preser - ved during ageing, despite the age-related losses on the field of cognitive and physical performance. Some researches has even shown the increases in social and emotional competencies, related with ageing. This increases are supposed to be the consequense of acummulated social experiences on one hand and a growing interest in achieving emotional well-being in the present, that replaces youthful interest in achieving succes in the future on the other hand. The purpose of our research was finding out, if ageing is associated with positive changes in social intelligence, emotional intelligence and the interpersonal relationships satisfaction on sample of Slovenian population. The sample consisted of 219 persons, aged 18 through 92. Participants completed instruments for measuring social intelligence (TSIS), emotional intelligence (ESCQ) and interpersonal relationships satisfaction (Positive relations with others scale - PWBS). The results show significant increase in social intelligence related with ageing.
Keywords: čustvena inteligentnost; medosebni odnosi; socialna inteligentnost; staranje